Determinasi Harga Saham Pada PT. Matahari Putra Prima, TBK. - Afdhatul Wahdaniyah; Puji Muniarty (Institut Bisnis dan Informatika Kesatuan, 2022)
The research objective is to analyze the effect of Return On Equity and Debt to Equity Ratio partially on stock prices at PT. Matahari Putra Prima Tbk, which is engaged in the retail sub-sector which has been listed since 1992. This type of associative research with a quantitative approach with research instruments in the form of a table list for (10) years from 2011 - 2020 in the form of financial statements consisting of balance sheets and profits make a loss. Methods of data collection with documentation and literature study, as well as the sampling used purposive sampling. Data analysis used classical assumption test, multiple linear regression, multiple coefficients, t test and f test. The sample used in this study was 10 with the period 2011-2020. The results showed that Return On Equity had a partially significant effect on stock prices and the Debt To Equity Ratio had no partially significant effect on stock prices. Then Return On Equity and Debt To Equity Ratio have a significant effect simultaneously on stock prices.